Response of Chir Pine (Pinus roxburghii Sarg.) Seedlings to Various Photoperiods - Bhatnagar, H. P.; Gupta, B. B.; Rauthan, B. S. (Indian Forester, 1970)
Pot cultare experiments were conducted to study the influence of difFerent photo-periodic treatments on the height growth of chir (Pinus roxburghii) seedlings. Significant differences were found in the height growth of seedlings among the four photoperiodic treatments, viz., long day of 18 hours, normal day of 11 to 14 hours, short day of 7 hours and intermittent day of 12 hours. Best height growth was recorded under long day treatment followed by intermittent day, then under normal day treatment and the poorest height growth was recorded under short day treatment.